Utilization of palm oilsludge in poultry diet: 3. Inclusion of fresh or dried fermented palm oil sludge in broiler’s diet - A.P Sinurat; Tatty Purwadaria; T Pasaribu; J Darma; I.A.K Bintang; M.H Togatorop (Indonesian Center for Animal Research and Development (ICARD), 2001)
Drying proces, especially with heating often affects the nutritive values of feed ingredients. Therefore, this experiment was designed to study the responses of broiler chickens when fed with ration containing fresh or dried fermented palm oil sludge(FPOS). Experimental diets with different levels of fresh or dried FPOS (5, 10, and 15% equally to dried FPOS) were formulated with similar nutrient contents. A control diet with no FPOS was also included. Each diet was fed to 30 broiler chickens (5 replicates of 6 birds) for 5 weeks. Performances (body weight, feed consumption, feed conversion, and mortalities) of chickens were recorded. Carcass percentage and abdominal fat content was also measured at the end of feeding trial. Data obtained were subjected to analysis of variance in a completely randomized design and different between means were tested by orthogonal contrast procedures. Results of the experiment showed that body weight gain (BWG) of control birds was not significantlydifferent with BWG of birds fed with FPOS. Birds fed with dried FLS gain more weight than those fed with fresh FPOS (1048 vs 981 g/bird). Increasing of dietary FPOS levels decreased BWG, but 10% inclusion was still tolerable. Feed consumption of control diet was significantly (P<0.05) less than feed consumption of diet with FPOS. Increasing of dried FPOS to 15% did not affect feed consumption, but increasing of fresh FPOS significantly increased feed consumption. Feed conversion (FCR) of control diet was significantly better than the FPOS diet (2.07 vs 2.13). Increasing levels of dried FPOS from 5 to 10% did not affect the FCR, but further increasing to 15% significantly worsen the FCR. Increasing of fresh FPOS from 5 to 10 or 15 significantly worsen the FCR. Dry matter intake, mortalities, carcass percentage, liver weight, and abdominal fat levels of broilers were not significantly affected by dietary treatments (P>0.05). Conversion of feed dry matter to body weight gain of control diet was not significantly (P>0.05) different with those diets with FPOS. However, dry matter conversion of dried FPOS was significantly better than the fresh FPOS. Increasing levels of FLS from 5 to 15 significantly worsen the feed dry matter conversion but not with inclusion of 10% FPOS. Therefore, it is concluded that there is no superior advantage of feeding fresh FPOS as compared with dried FPOS. Inclusion of 10% dried or fresh FPOS in the diets did not affect growth performances of broiler chickens. Key words: Palm oil sludge, dried, fermented, broilers